Assessment of Stormwater Runoff Quality in Various Location in University Campus - Hazizan A.A.; Ahmed A.N.; Hayder G. (Springer, 2023)
Sampling of urban stormwater runoff was carried out in a few small catchment area in UNITEN. The objectives of this study are to investigate the stormwater runoff quality in various location in UNITEN. The area represents different type of landuses such as residential (Cendekiawan Apartment), commercial (UNITENs Cafe) and industrial (construction site near to College of Engineering (COE) parking area). Twelve runoff samples from three different location were analyzed. Stormwater runoff quality shows large variations in concentration during storms, especially for total suspended solid (TSS), BOD5, COD and turbidity. TSS for construction site was the highest which are 36123mg/L. BOD5 for UNITENs Caf was the highest with 165mg/L. COD for both construction site and UNITENs caf were exceed the limit with 1421mg/L and 989mg/L respectively. pH measurement shows acceptable result for some locations. Event mean concentration (EMC) was evaluate and compared to mean EMC values by Department of Irrigation and Drainage (DID). Recommendation was made to improve the water quality in the future. 2020, Springer Nature Singapore Pte Ltd.